2015
DOI: 10.1186/s13068-015-0324-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Escherichia coli for production of (2S,3S)-butane-2,3-diol from glucose

Abstract: BackgroundButane-2,3-diol (2,3-BD) is a fuel and platform biochemical with various industrial applications. 2,3-BD exists in three stereoisomeric forms: (2R,3R)-2,3-BD, meso-2,3-BD and (2S,3S)-2,3-BD. Microbial fermentative processes have been reported for (2R,3R)-2,3-BD and meso-2,3-BD production.ResultsThe production of (2S,3S)-2,3-BD from glucose was acquired by whole cells of recombinant Escherichia coli coexpressing the α-acetolactate synthase and meso-butane-2,3-diol dehydrogenase of Enterobacter cloacae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…One method to generate S,S-2,3-butanediol is by employing E. coli as a biocatalyst to recycle meso-2,3-butanediol and convert it to S,S-2,3butanediol (J. et al, 2010). Alternatively, the 2,3-butanediol pathway can be reengineered without acetolactate decarboxylase, thereby obtaining in vivo diacetyl biosynthesis through non-enzymatic decarboxylation of acetolactate (Chu et al, 2015). The same study has shown that addition of Fe 3+ aids decarboxylation and achieved enantiomerically pure S,S-2,3-butanediol production up to 2.2 g/L.…”
Section: Diolsmentioning
confidence: 99%
“…One method to generate S,S-2,3-butanediol is by employing E. coli as a biocatalyst to recycle meso-2,3-butanediol and convert it to S,S-2,3butanediol (J. et al, 2010). Alternatively, the 2,3-butanediol pathway can be reengineered without acetolactate decarboxylase, thereby obtaining in vivo diacetyl biosynthesis through non-enzymatic decarboxylation of acetolactate (Chu et al, 2015). The same study has shown that addition of Fe 3+ aids decarboxylation and achieved enantiomerically pure S,S-2,3-butanediol production up to 2.2 g/L.…”
Section: Diolsmentioning
confidence: 99%
“…Therefore, the other two important genes, budB and budC, responsible for 2,3-BD production should be inserted into the glycerol metabolism pathway of E. coli BL21(DE3)pLysS/dhaD stain to get a high yield of 2,3-BD. Although there is no report on the pathway of 2,3-BD production in E. coli, several works have been done on systematic metabolic engineering of E. coli for high product yield of 2,3-BD by introducing budB and budC genes (Xu et al 2014;Chu et al 2015).…”
Section: Batch Fermentation By the Recombinant E Coli Bl21(de3) Plysmentioning
confidence: 99%
“…Both myo-inositol and butane- 2,3- diol, products of glucose metabolism demonstrated significant change in abundance due to ZIKV infection ( Figure 2I ). Butane- 2,3 – diol, a volatile compound associated with certain strains of root-associated bacteria ( Kong et al, 2018 ) and capable of being produced from glucose ( Chu et al, 2015 ) was highly abundant ( P = 0.013; Log 2 5 fold change) in the infected samples ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%